The populist politics of Euroscepticism in times of crisis: A framework for analysis. (August 2018) - Pirro, Andrea LP; Taggart, Paul
The European Union has been recently exposed to the multiple shocks of the Great Recession, the migrant crisis, and Brexit. Populist parties have been, either directly or indirectly, considered the principal beneficiaries of these crises in light of their Eurosceptic profiles. In this introductory article, we lay out the conceptual and analytical tools necessary to identify populist Eurosceptic actors, and systematically tackle the under-explored link between populist Eurosceptic framing and the unfolding of the different European crises. While we provide a framework to assess (alleged) changes in the framing of these parties, we also contend that these parties may have released effects in the political process by conditioning shifts in the positions on Europe of their mainstream competitors. In doing so, we define a set of possible interactive scenarios.